A new species of Dugesia (Platyhelminthes, Tricladida, Dugesiidae) from the Afromontane forest in South Africa, with an overview of freshwater planarians from the African continent - Stocchino, Giacinta Angela; Sluys, Ronald; Manconi, Renata (Zootaxa, 2012)
A new species of the genus Dugesia from the Amatola Mountains in the Eastern Province of South Africa is described,including a karyological account and notes on its life cycle and reproductive modes. The new species differs from itscongeners in a unique combination of morphological characters of the copulatory apparatus, in particular the centralcourse of the ejaculatory duct with its terminal opening at the tip of the penis papilla, the elongated seminal vesicle, theasymmetrical openings of the oviducts into the bursal canal, and the openings of vasa deferentia at about halfway alongthe seminal vesicle. In addition, an overview is provided of all freshwater triclads reported from the African continent including karyological information and notes on reproductive modes.